Perceived Effect of Knowledge Level and Socio-Demographics on COVID-19 Risk Exposure: the Africa Experience - Obioma, Azuonwu; Nnenna, Ihua; Christian, Ahiakwo (International Journal of Coronaviruses, 2020)
COVID-19 remains a global public health emergency till date. It is eminent that the transmission of the disease is subjective to people’s readiness to implement public health preventative strategies and these are often related to knowledge. Proper public knowledge about COVID-19 plus its predisposing factors is critical to effectively manage the increasing public health risks. However, socio-demographics have been implicated to COVID-19 infection risk and management outcome. Thus, this present study examined the influence of knowledge on COVID-19 risk outcome, the contribution of socio-demographics on the risk of COVID-19 and predicted synergistic effects of knowledge and socio-demographics on the risk of COVID-19. All measured was strictly perception amongst African sampled with an online Google form as the primary data source. The Correlation designed used Zr Statistics of Fisher Transformation to determine the differences between the two correlation coefficients of the prediction variables after an initial test using Pearson Product Moment Correlation between COVID-19 risk and Knowledge plus socio-demographic. The hypothesis was tested using Statistical Package for Social Science version 21 and iStat at varying significant levels of 0.05 and 0.01 respectively. Generally, a significant relationship exists between COVID-19 risk and knowledge level but not with composite socio-demographics. However, specific significant relationship (p<0.05) was noticed between COVID-19 risk and age (r=0.220) as well as marital status (r=-0.158). Educational level, location, and sex showed no correlation (p>0.05) with COVID-19 exposure. Also, the proposition of no significant difference between correlation coefficients of socio-demographics and knowledge was proven otherwise (p<0.05). The regression model (R2=0.420 and adjusted R2=0.404, df=2, 336, F-value=27.012. p=0.00) significantly predicted the synergic contributions of knowledge level and socio-demographics to COVID-19 exposure. 40.04% of the COVID-19 risk exposure can be explained by socio-demographics and knowledge about COVID-19. Synergic contribution of knowledge and socio-demographics proved risk prediction to COVID-19. Traditional factor like age should be decidedly considered and attention should be drawn towards good knowledge about COVID-19 especially its signs and symptoms plus transmission.
Keywords: COVID-19; Knowledge Level; Socio-Demographics; Risk Exposure; Public Health